Educação infantil e contação de hitórias: memórias e práticas - Rosa, Claudia Belardinelli da (Universidade do Vale do Rio do Sinos, 2007)
Storytelling is considered an essential activity for children’s development. From this perspective, doubtless, the teacher’s role as “storyteller” is very significant, especially during the first years of education. This dissertation examine the subject from a research that presented the following questions: What is the purpose of storytelling by primary education teachers? Would your own memories help for such practice? Is story telling getting more meaningful in teacher formation courses? For this reason, a group of teachers was interviewed and they recalled their childhood, bringing back memories from stories they heard, about who told those stories and how they were told. They also described their actual pedagogic practices related to storytelling. The study analyzed narratives of spoken accounts as well as questionnaires applied in teacher training schools. Among the conclusions were: during their childhood teachers listened to stories, which was a positive experience they kept in their memory; teachers
Keywords: educação infantil; formação de professores; memórias; prática; contação de histórias; children education; memory; practice; teacher formation; storytelling; Ciências Humanas